2003
DOI: 10.1128/ec.2.5.1061-1068.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sfp1 Plays a Key Role in Yeast Ribosome Biogenesis

Abstract: Sfp1, an unusual zinc finger protein, was previously identified as a gene that, when overexpressed, imparted a nuclear localization defect. sfp1 cells have a reduced size and a slow growth phenotype. In this study we show that SFP1 plays a role in ribosome biogenesis. An sfp1 strain is hypersensitive to drugs that inhibit translational machinery. sfp1 strains also have defects in global translation as well as defects in rRNA processing and 60S ribosomal subunit export. Microarray analysis has previously shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 29 publications
(49 reference statements)
7
135
0
1
Order By: Relevance
“…In addition to Ras/protein kinase A and TOR, Sfp1 and Sch9 are likely involved in coordinating the expression of these two networks, given their role in dictating critical cell size at the G 1 /S transition and coordinating the expression of genes for ribosomal biogenesis (22,43,59). Although few of the genes encoding structural components of the ribosomes were significantly (P Ͻ 0.01) affected here, many (ϳ80) do show a kinetically similar trend of down-regulation but with lower confidence (P Ͼ 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Ras/protein kinase A and TOR, Sfp1 and Sch9 are likely involved in coordinating the expression of these two networks, given their role in dictating critical cell size at the G 1 /S transition and coordinating the expression of genes for ribosomal biogenesis (22,43,59). Although few of the genes encoding structural components of the ribosomes were significantly (P Ͻ 0.01) affected here, many (ϳ80) do show a kinetically similar trend of down-regulation but with lower confidence (P Ͼ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Such a transcriptional program makes functional sense given the acute interruption in the steady-state rate of energy production during the switch from mixed respirofermentative to strictly fermentative growth in galactose. Although no factors have been identified that directly bind to PAC or RRPE, Sfp1, and/or Sch9 are likely involved given their role in regulating nucleolar genes for ribosomal biogenesis and translation at START (22,43,59).…”
Section: Figmentioning
confidence: 99%
“…Regulation of expression of the ribosome biogenesis regulon (RiBi) and the ribosomal proteins themselves has recently been elucidated in yeast (Jorgensen et al, 2002) with the discovery of two transcription factors, Sfp1 and Sch9, which function in the Ras/PKA and TOR signaling pathways to control the ribosome biosynthetic rate (Fingerman et al, 2003;Jorgensen et al, 2004a;Marion et al, 2004). It has been proposed that expression of the RiBi regulon also affects the cell size setpoint for Start, because mutations that inhibit RiBi expression result in small cells passing Start (Jorgensen et al, 2002;Jorgensen and Tyers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The forkhead-like protein Fhl1 and an interacting factor Ifh1 constitute one axis of RP gene regulation Schawalder et al, 2004;Wade et al, 2004;Rudra et al, 2005). A second regulator that localizes to RP gene promoters is the split Zn-finger transcription factor Sfp1 (Fingerman et al, 2003;Jorgensen et al, 2004;Marion et al, 2004). RP gene expression is regulated by PKA through both Fhl1 and Sfp1 (Jorgensen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%